Peran Perguruan Tinggi dalam Membangun Budaya Keterbukaan Informasi Publik - afrizal tjoetra (Prodi Sosiologi FISIP Universitas Teuku Umar, 2018)
The purpose of this study is to determine the readiness of universities in implementing the Public Information Disclosure Act and the role that can be taken by universities to build a culture of public information disclosure. This study uses qualitative methods through literature review. The main documents referred to are books, laws, Information Commission regulations, as well as evaluation reports conducted by the Central Information Commission and the Aceh Information Commissio. Based on the results of the study it is known that the readiness of universities in implementing the Public Information Disclosure Act is still not in accordance with the provisions. There are still a number of challenges that must be managed jointly internally as well as the support of other components. Next, the role that universities can play in building a culture of public information disclosure can be carried out through 3 things, namely as a